Improving Community Health Literacy through Acute Respiratory Infection Prevention Education - Marisa Marcelina Limbong; Pipih Salanti; Anggarani Prihantiningsih (ADI Pengabdian Kepada Masyarakat, 2026)
Acute Respiratory Infection (ARI) remains an important public health concern, particularly when community knowledge regarding risk factors, signs and symptoms, and prevention is limited. This community service program aimed to improve community health literacy on ARI prevention in RT 12 RW 01, Jagakarsa Urban Village, Jagakarsa District, South Jakarta. The program was conducted from 9 to 27 March 2026 using the Healthy Indonesia Program with a Family Approach (PIS-PK). Health problems were identified through surveys, interviews, and observations involving 135 respondents, while the CARL method was used to determine the priority problem. The assessment identified limited community knowledge of ARI as a priority issue. In addition, 11 ARI cases were recorded in the target area, consisting of 6 females (55%) and 5 males (45%). The priority problem was addressed through face-to-face health education covering ARI, risk factors, signs and symptoms, transmission, and preventive measures. The activity was well implemented and received positive community participation. These findings indicate that health education based on identified community needs can support ARI prevention efforts. Future activities should include regular education, involvement of health cadres and local health services, and measurable evaluation using pre-test and post-test assessments.